2016
DOI: 10.1111/pedi.12461
|View full text |Cite
|
Sign up to set email alerts
|

Low association between fasting and OGTT stimulated glucose levels with HbA1c in overweight children and adolescents

Abstract: Because FPG, 2-hour glucose, and HbA1c correlated only weakly we propose that these parameters, particularly in the normal range, might reflect distinct aspects of carbohydrate metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…There was only a weak correlation between FPG, 2-hr PG, and HbA1c in German children and adolescents. 29 Only 7% of 4,004 European adults satisfied all three tests. 30 The discrepancy between HbA1c level and OGTT results was more remarkable in prediabetes than in diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…There was only a weak correlation between FPG, 2-hr PG, and HbA1c in German children and adolescents. 29 Only 7% of 4,004 European adults satisfied all three tests. 30 The discrepancy between HbA1c level and OGTT results was more remarkable in prediabetes than in diabetes.…”
Section: Discussionmentioning
confidence: 96%
“…When the ADA criteria were followed, there was a limited association between impaired fasting glucose and further metabolic derangement in our cohort, suggesting that, at least in children, the WHO criteria for impaired fasting glucose may be more suitable to address patients at risk of metabolic disturbances. Indeed, the postulated clinical relevance of isolated impaired fasting glucose or HbA1c 5.7% to 6.4% for risk of further metabolic derangement in childhood obesity is not only questionable, but apparently inexistent according to the data presented here. Hence, it should probably not be considered as diagnostic criteria in this age range, thus avoiding unnecessary complementary tests and psychological stress for patients and families.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a large study of youth with overweight and obesity (n = 4848) showed only weak correlations between HbA1c and FPG (r = 0.18) and HbA1c and 2-hour OGTT glucose (r = 0.17). 35 It is clear that these measures-FPG, OGTT, and HbA1c-reflect distinct aspects of carbohydrate metabolism and resulting glycemia, and that these are associated with the discrepancies with the other 2 measures. Moreover, in some youth, the 75 g of dextrose present in an OGTT is less than the glycemic load they typically consume in one sitting.…”
Section: Meƞormin Dosingmentioning
confidence: 99%